Secret hero society. Fort solitude - Fridolfs, Derek (Scholastic Inc., 2017)
Young Clark Kent is thrilled to join a spring break academic retreat at Camp Evergreen. But when kids start disappearing, Clark, Bruce, and Diana team up to take on bigfoot, a lake monster, and rumors of a UFO that crashed into the lake.